D8 Open Data for Agriculture Presentation by Melanie Bacou, IFPRI, HarvestChoice - Bacou, Melanie (2013)
Presentation by Melanie Bacou at the D8 Open Data for Agriculture Side event at IFPRI on May 1, 2013.